Analysis of microRNA expression profiles in human bronchial epithelial cells infected by Chlamydia psittaci. (May 2021) - Liu, Luyao; Chen, Xi; Tang, Ting; Chen, Li; Huang, Qiaoling; Li, Zhongyu; Bai, Qinqin; Chen, Lili
Abstract: Background: Chlamydia psittaci is a pathogen of birds that can cause zoonotic disease in mammals including pneumonia in humans. MicroRNAs (miRNAs) are a class of small non-coding RNA fragments with a length of about 22 nt, which play an important role in regulating gene expression after transcription. Chlamydia infection can cause changes in host cell miRNA expression, but the potential biological function of miRNAs in C. psittaci infection and pathogenesis is not well understood. Methods: Small RNA sequencing (sRNA-Seq) technology was used to characterise miRNA expression in human bronchial epithelial (HBE) cells after C. psittaci infection, and differentially expressed miRNAs were identified. Candidate target genes for these miRNAs were then functionally annotated by Gene Ontology (GO) analysis and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis. The sRNA-Seq results were partially validated by quantitative real time polymerase chain reaction (qRT-PCR) and miRNA-target networks were constructed using visualization software. Results: We identified 151 differentially expressed miRNAs (46 known miRNAs and 105 novel miRNAs) in C. psittaci -infected HBE cells, of which 140 were upregulated and 11 were downregulated. Of these, 17 known miRNAs were significantly upregulated and two were downregulated using P < 0.05 and |log2 FoldChange|>1.5 as threshold criteria. GO enrichment results showed that the predicted targets of these differentially expressed miRNAs were mainly involved in transcriptional regulation and ATP binding. KEGG pathway analysis suggested that the candidate target genes were involved in several important signaling pathways such as MAPK, ErbB, cGMP-PKG, cAMP, mTOR, GNRH, oxytocin, PI3K-Akt and AMPK, which are primarily related to biological processes such as transcription and signal transduction. The qRT-PCR results for miR-2116–3p, miR-3195, miR-663a, miR-10401–5p, miR-124–3p, miR-184, miR-744–5p and hsa-miR-514b-5p were consistent with the sRNA-Seq data. Conclusions: A large amount of miRNA expression profile data relating to C. psittaci infection was obtained, which provides a useful experimental and theoretical basis for further understanding the pathogenic mechanisms of C. psittaci infection. Highlights: Detection of the differential expression Profiles of miRNAs in Chlamydia psittaci infected HBE cells. There are 151 differentially expressed miRNAs in C. psittaci infected HBE cells (140 upregulated and 11 downregulated). HBE cells could be regulated by the differentially expressed miRNAs to affect the infectivity of C. psittaci.